Assessment of flexible interconnection strategies for the integration of electric vehicles and renewable energy in load-centric distribution networks - Guowei Liu; Liming Wang; Kangsheng Cui; Peiqian Guo; Hao Dai; Min Guo; Lisheng Xin (Global Energy Interconnection)
Flexible interconnection devices (FIDs) significantly enhance the regulation and management of complex power flows in distribution networks. Voltage source converter (VSC)-based FIDs, in particular, are pivotal for increasing system reliability and operational efficiency. These devices are crucial in supporting the extensive incorporation of electric vehicles (EVs) and renewable energy sources (RESs) into new, load-centric environments. This study evaluates four unique FID-based configurations for distribution network interconnections, revealing their distinctive features. We developed a comprehensive evaluation framework and tool by integrating the analytic hierarchy process (AHP) and fuzzy comprehensive evaluation (FCE), which includes five key performance indicators to assess these configurations. The study identifies the optimal application scenarios for each configuration and discusses their roles in enabling the seamless integration of EVs and RESs. The findings provide essential insights and guidelines for the design and implementation of adaptable, interconnected distribution networks that are equipped to meet the growing demands of future urban environments.